Pengaruh Pengendalian Akuntansi, Sistem Pelaporan, Dan Kejelasan Sasaran Anggaran Terhadap Akuntanbilitas Kinerja Instansi Pemerintah di Kantor Pertanahan Nasional Boyolali - Eko Dini Ratmawati; Muhammad Hasan Ma'ruf; Wikan Budi Utami (Nur Science Institute, 2026)
This study aims to examine the effects of budget target clarity, accounting control, and reporting systems on the performance accountability of government agencies at the National Land Agency Office of Boyolali Regency. This study employed a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 55 respondents selected using purposive sampling and analyzed using multiple linear regression with IBM SPSS. The results indicate that accounting control and reporting systems have a positive and significant effect on the performance accountability of government agencies, whereas budget target clarity has no significant effect. These findings suggest that effective accounting control and high-quality reporting systems are more closely associated with improving performance accountability in the research setting. This study contributes empirical evidence to the public sector accounting literature and provides practical insights for strengthening government performance accountability.